Migration of lipid and other components and formation of micro/nano-sized colloidal structure in Tuna (Thunnus obesus) head soup. (August 2019) - Qian, Xueli; Fan, Xinyi; Su, Hong; Zhang, Jing; Tao, Ningping; Zhong, Jian; Wang, Xichang; Han, Bingshe
Abstract: It was aimed to study the migration of lipid and other substances in the tuna head soup, the formation and change of colloidal structures and the interaction between their components. The results indicated that the contents of saturated fatty acids, monounsaturated fatty acids, and poly unsaturated fatty acids both in the broth and pan-fried soup (PFS) reached the maximum with the ratio of fish head pieces to water 1:8, boiling at temperature 90 ± 2 °C for 150 min. In addition, the migration concentrations of lipid and other components in the PFS were higher than that in the broth during cooking process. The results of morphological characteristics of particles indicated that a large number of stable bilayer spherical particles were formed both in the broth and PFS after boiling for 150 min. Analysis of chemical components composition of microstructure in the bigeye tuna head soup showed that unequal-sized triglycerides and protein particles were found while polar lipids and carbohydrates moieties were almost dispersed around particles. These results suggest that a complex colloid structure is formed in the soup due to the migration of lipid and other compounds present in the tuna head. Highlights: FAs reached maximum with tuna head to water 1:8, boiling at 90 ± 2 °C for 150 min. Migration of lipids and others in pan-fried soup were higher than in broth. Micro/nano-sized colloidal structure analyzed by LSCM. Polar lipids and carbohydrates dispersed around TAG and protein particles.